2015
DOI: 10.1614/ws-d-14-00162.1
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Spotted Spurge (Chamaesyce maculata) Seeds in Response to Different Environmental Factors

Abstract: Spotted spurge, a C4species, is a summer annual weed, introduced to the Golestan province of Iran in 2006. A series of laboratory experiments were conducted at the Faculty of Agriculture, Ferdowsi University of Mashhad, Iran, to evaluate the influence of environmental factors on seed germination of spotted spurge. Seeds germinated over a constant temperature range of 25 to 45 C with a 14-h photoperiod and at 30 to 50 C in continuous darkness. Seeds germinated at alternating day/night temperature regimes of 25/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 42 publications
3
31
0
Order By: Relevance
“…Light was not required for the germination of M. perfoliatum. In contrast, several researchers have reported that the seed germination of some weed species can be stimulated by light (Chauhan et al 2006b;Del Monte & Dorado 2011;Ahmed et al 2015;Asgarpopur et al 2015). Ohadi et al (2011) demonstrated that turnipweed seeds are photosensitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Light was not required for the germination of M. perfoliatum. In contrast, several researchers have reported that the seed germination of some weed species can be stimulated by light (Chauhan et al 2006b;Del Monte & Dorado 2011;Ahmed et al 2015;Asgarpopur et al 2015). Ohadi et al (2011) demonstrated that turnipweed seeds are photosensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the survival of annual weeds in agroecosystems highly depends on seed dormancy (Defelice 2003;Taab & Andersson 2009;Stanton et al 2012) or on the formation of a soil seed bank (Egley & Chandler 1978;. Factors, such as the temperature (Fandrich & Mallory-Smith 2005;Foley 2008), light (Huebner 2011), pH (Asgarpopur et al 2015), osmotic potential (Boyd & Van Acker 2004), soil salinity (Zhou et al 2005), seed burial depth (Penny & Neal 2003;Wilson et al 2006), KNO 3 (Fawcett & Slife 1978) and GA 3 (Ren & Guan 2008), can highly affect seed germination. However, little is known about how these factors influence the germination of M. perfoliatum.…”
mentioning
confidence: 99%
“…The rate of seed imbibition decreases with decreasing soil water potential, causing a water deficit and, consequently, decreased germination (Asgarpour et al 2015). In our study, B. sterilis seeds germinated within 1 day at the optimal temperature and without water stress, but the effect of insufficient imbibition at lower Ψ on T 50 was clearly visible at the lowest temperature in L, which prolonged the T 50 by about 5-6 days.…”
Section: Discussionmentioning
confidence: 41%
“…Soil water potential is one of the factors that regulate seed water uptake. The rate of seed imbibition decreases with decreasing soil water potential causing a water deficit and, consequently, the decreased germination (Asgarpour et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Goubitz et al (2003) concluded that high pH negatively affects seed germination of Pinus halepensis. On the other hand, some research has revealed that soil pH is not a limiting factor for many species of plants, such as spotted spurge (Chamaesyce maculata) (Asgarpour et al 2015), buffalobur (Solanum rostratum) (Wei et al 2009), cadillo (Urena lobata) (Wang et al 2009), sheep sorrel (Rumex acetosella) ) and hoary cress (Rezvani & Zaefarian 2016). Consequently, germination over a wide pH range indicates that pH would not be a limiting factor for colonizing different habitats for these species.…”
Section: Discussionmentioning
confidence: 99%